A knowledge management architecture for information technology services delivery - Almeida, Tiago Nobre Lopes de (My University, 2018)
Knowledge Management is a scientific area related to the organizational value of knowledge and is understood as a multidisciplinary field of research. Notions and practices are emerging and incorporated in organizations in different areas, as is the case of IT Service Management. Today’s business environment is increasingly unstable, characterized by uncertainties and changes, where technology changes rapidly, competitors multiply, and products and services quickly become obsolete. In this context, management is increasingly focused not only on people management, but on the knowledge they have and how to capture it. An Information System aligned with Knowledge Management and Intellectual Capital aims to represent and manage explicitly the different dimensions associated with an organizational competence. If organizations integrate Knowledge Competencies, Knowledge Engineering, Information Systems and Organizational Memories, these will improve the organization's knowledge and subsequently improve the quality of the service provided to users and customers. This research will use Design Science Research methodology to create an artifact to be applied in a case study from an organization aligned with ITIL best practices. This organization is supported by an Intranet and an ERP for laptop repair process. The outcome of this dissertation aims to demonstrate if Knowledge Management improves the IT services delivery.
Keywords: Knowledge Management; Knowledge Engineering; Organizational Memories; Intranet Management; IT Service Management; Service Delivery